Antisense RNA regulation and application in the development of novel antibiotics to combat multidrug resistant bacteria. (28th March 2013) - Ji, Yinduo; Lei, Ting
Despite the availability of antibiotics and vaccines, infectious diseases remain one of most dangerous threats to humans and animals. The overuse and misuse of antibacterial agents have led to the emergence of multidrug resistant bacterial pathogens. Bacterial cells are often resilient enough to survive in even the most extreme environments. To do so, the organisms have evolved different mechanisms, including a variety of two-component signal transduction systems, which allow the bacteria to sense the surrounding environment and regulate gene expression in order to adapt and respond to environmental stimuli. In addition, some bacteria evolve resistance to antibacterial agents while many bacterial cells are able to acquire resistance genes from other bacterial species to enable them to survive in the presence of toxic antimicrobial agents. The crisis of antimicrobial resistance is an unremitting menace to human health and a burden on public health. The rapid increase in antimicrobial resistant organisms and limited options for development of new classes of antibiotics heighten the urgent need to develop novel potent antibacterial therapeutics in order to combat multidrug resistant infections. In this review, we introduce the regulatory mechanisms of antisense RNA and significant applications of regulated antisense RNA interference technology in early drug discovery. This includes the identification and evaluation of drug targets in vitro and in vivo, the determination of mode of action for antibiotics and new antibacterial agents, as well as the development of peptide-nucleic acid conjugates as novel antibacterials.